Evaluation of Lipofilling Safety in Elderly Patients with Breast Cancer. Issue 7 (July 2015) - Chirappapha, Prakasit; Rietjens, Mario; De Lorenzi, Francesca; Andrea, Manconi; Hamza, Alaa; Petit, Jean-Yves; Garusi, Cristina; Martella, Stefano; Barbieri, Benedetta; Gottardi, Alessandra
Abstract : Background: Lipofilling is widely used in breast reconstruction after mastectomy with reconstruction or breast conserving surgery in patients with breast cancer. The aim of this study is focused on complications associated with lipofilling in elderly breast cancer patients with breast defects after breast conserving surgery or reconstruction. Methods: A total of 137 patients older than 60 years who underwent 153 lipofilling procedures were included. All patients had undergone breast lipofilling using Coleman's technique. Estimated breast defect volume, lipofilling volume, and complications after lipofilling were obtained for analysis. Results: Most patients (67%) had only 1 lipofilling procedure. The median lipofilling volume to breast defect volume ratio was 1.5. No severe complications were found after treatment. Liponecrosis was detected in 10 of 153 breasts (7%) or 9 of 137 patients within 2 weeks after lipofilling and required surgical drainage in 2. No local recurrences were noted. Conclusions: The incidence of liponecrosis after lipofilling in elderly patients was relatively high, requiring surgical drainage in some cases. As a rough guide, the lipofilling volume should not exceed 1.5 times the defect volume, and close postoperative follow-up within the first 2 weeks is suggested for these patients.